Regímenes de regulación del riesgo: una aproximación conceptual para observar América Latina - Sáez Ardura, Felipe; Vallejos-Romero, Arturo (Revista del CLAD Reforma y Democracia, 2019)
AbstractThis article aims to present the so-called Regulation Regimes Approach (ERR by its acronym in Spanish) which, developed on the basis of a sociology of regulation, provides conceptual tools that would allow a deep and novel analysis of the problems that Latin America is experiencing in the field of social regulation, especially in the socio-environmental dimension. For this purpose, an epistemic movement is proposed in two moments with the intention of opening risks domains little explored by Latin American social sciences in the path of environmental sociology. The use of the notion of “concentric societies” is advocated, which provides a distinctive component of risk for Latin America. The conclusions suggest that the ERR could become a fruitful sociological work model for the study of risks, specifically in those that go beyond the control of institutions, projecting as regulatory capacities of social institutions to define, manage and control risks.
Keywords: Risk; Risk Management; Regulation Process; Social Analysis; Latin America